Peningkatan Keterampilan Berbicara dengan Metode Reka Cerita Gambar pada Siswa Kelas 4A SD Negeri Kroyo Sragen - Ajeng Pangesti; Agus Darmuki; Nur Alfin Hidayati (Universitas Sarjanawiyata Tamansiswa, 2018)
This study aims to improve the students' speaking skills with the method of inventionÂ picture stories for grade 4A students of SD Negeri Kroyo Karangmalang Sragen. This type of research is classroom action research in 2 cycles with stages of planning, implementing, observing, and reflecting. Data collection techniques use observation, documentation, and test techniques. Data validation uses data triangulation and method triangulation. The results showed pre-action learning average scores of students reached 52.9 classical completeness 59.1%, first cycle 76.4 with classical completeness 81.8%, and the second cycle increased to 80.8, with classical 100%. Conclusions show that the application of speaking skills with the method of inventionÂ picture stories can improve students' speaking skills.